Functionalized Mesoporous MCM-41 as a Hybrid Catalyst for the Efficient Synthesis of Chromene and Mono/Bis Phthalazine-Trione Derivatives. (2nd January 2023) - Bodaghifard, Mohammad Ali; Zendehdel, Mojgan; Hamidinasab, Mahdia; Ahadi, Najmieh; Zandi, Raziyeh
Abstract: Hybrid structures containing organic-inorganic porous materials are of substantial interest as green, heterogeneous and recyclable catalysts. In this study, an organic-inorganic hybrid material is prepared by surface functionalization of mesoporous MCM-41 with organic tags. The structure of hybrid material was characterized using the Fourier-transform infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray spectroscopy (EDS), thermogravimetric analysis (TGA). Subsequently, the catalytic activity of this novel hybrid material was investigated in the efficient one-pot, multicomponent reactions (MCRs) for synthesis of 2-amino-4 H -chromenes and mono/bis phthalazine-triones under environmentally benign conditions. The most important advantages of this work are mild and green conditions, short reaction time, high efficiency and excellent yields of desired products. Moreover, the hybrid catalyst could be recycled up to four reaction runs with slight loss of the catalytic activity.